What affects the uptake of screening for bowel cancer using a faecal occult blood test (FOBt): A qualitative study - Chapple, A; Ziebland, S; Hewitson, P; McPherson, A (Elsevier, 2008)
Screening can reduce bowel cancer mortality. The UK National Health Service Bowel Cancer Screening Programme (NHS BCSP), using the Faecal Occult Blood test (FOBt), is being introduced over three years in the UK, but in some areas uptake is disappointing. We sought to understand why some people decided to participate in screening for bowel cancer while others did not. Interviews were conducted with 44 men and women invited for screening. Most had decided to take part, some were reluctant, and a few had declined to participate. We aimed for a maximum variation sample. Reasons for accepting screening included: knowing someone with cancer, previous positive experience of women's screening programmes, being a "good citizen", previous bowel problems, and encouragement from others. Reasons for reluctance to take part included: feeling healthy, fear of outcome, lack of time, disgust at the idea of handling stools, concern about posting samples in the mail, misunderstanding instructions, and past (negative) experience or fear of colonoscopy. Theoretical models of health behaviours do not mention the sense of civic responsibility that encourages people to avert (later) costs to the NHS. This may be a particular feature of a socialized health system. Our results also suggest that people might feel more inclined to accept screening if they had current information about patients' experiences of colonoscopy and treatment for early bowel cancer.